Computational Model of Magnesium Deposition and Dissolution for Property Determination via Cyclic Voltammetry. Issue 9 (1st January 2016) - Chadwick, Alexander F.; Vardar, Gulin; DeWitt, Stephen; Sleightholme, Alice E. S.; Monroe, Charles W.; Siegel, Donald J.; Thornton, Katsuyo
Abstract : The development of a practical magnesium-anode battery requires electrolytes that allow for highly efficient magnesium exchange while also being compatible with cathode materials. Here, a one-dimensional continuum-scale model is developed to simulate cyclic plating/stripping voltammetry of a model magnesium-based electrolyte system employing magnesium borohydride/dimethoxyethane [Mg(BH4 )2 /DME] solutions on a gold substrate. The model is developed from non-electroneutral dilute-solution theory, using Nernst-Planck equations for the mass flux and Poisson's equation for the electrostatic potential. The electrochemical reaction is modeled with multistep Butler-Volmer kinetics, with a modified current/overpotential relationship that separately accounts for the portions of the current responsible for nucleating new deposits and propagating or dissolving existing ones. The diffusivities of the electrolyte species, standard heterogeneous rate constant, charge-transfer coefficient, formal potential, and nucleation overpotential are determined computationally by reproducing experimental voltammograms. The model is computationally inexpensive and therefore allows for broad parametric studies of electrolyte behavior that would otherwise be impractical.